Unilateral Lichen Aureus in a Child - Case Report - Heliana Freitas de Oliveira Góes; Marília Troyano de Castro Mendes; Aline Falci Loures; Ada Lobato Quattrino; Caren dos Santos Lima; Luciana Pantaleão (Journal of the Portuguese Society of Dermatology and Venereology, 2016)
Lichen aureus is a subtype of a chronic benign pigmented purpuric dermatosis of unknown etiology. It shows predilection for lower limbs and generally affects young adults and, less often, children. We report a case of lichen aureus with a unilateral presentation in a child.